THE EFFECT OF NATIONAL SOCIAL INVESTMENT PROGRAMS AGENCY ON POVERTY REDUCTION IN SOUTH EAST NIGERIA - Hillary Anikeze, Nnaemeka; Chinelo Onyema, Sylvia; Chukwuebuka Okoloagu, Colin (African Journal of Social and Behavioural Sciences, 2024)
This study investigated the Effect of the National Social Investment Programs Agency on Poverty Reduction in South East Nigeria from 2015 - 2023. Specifically, the study is designed to examine the effect of the N-power program on job creation in Southeast East Nigeria, ascertain the effect of the Government Enterprise and Empowerment program in enhancing small-scale business in Southeast East Nigeria, determine the effect of conditional cash transfer in addressing income inequality in south East Nigeria. The study was carried out in five randomly selected major cities in South East Nigeria (Enugu, Umuahia, Abakaliki, Anambra, and Owerri). The study employed survey research method. The population for the study comprised eight hundred and seventy-six (2876) residents in the five selected major cities in South East Nigeria, while three hundred and fifty-one (351) respondents were sampled using Taro Yamane sampling techniques. A questionnaire designed by the researcher served as the instrument for data collection. The data collected were analysed using simple percentages while the hypotheses were tested at 0.05 level of significance using chi-square. The findings of the study revealed that the National Social Investment Program has a positive significant effect in enhancing the standard of living in South East Nigeria; the National Social Investment Program has a positive significant effect in creating job opportunities in South East Nigeria. Based on the findings of the study, the following recommendations were made: national social investment agency should develop programs that are tailored to the specific needs and challenges of South East Nigeria, which will help address the succession agitation in the area; local communities should be actively engaged in planning and implementation of social investment programs; national social investment program should focus in investing in education and vocational training programs to equip individuals with the skill needed for gainful employment.